ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Alvro Mizardi; Melinda Rismawati; R Andy Pranando (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
The purpose of this study is to analyze how the ability of the students of SMA Negeri 1 Sungai Tebelian for the academic year 2021/2022, the research subjects were 16 students of class X IPA1 semester 2. The data collected was in the form of data on students' ability tests in mathematical communication in solving problems. or solve problems presented in the form of stories by communicating everyday language into mathematical language. The test questions used to measure students' mathematical communication skills consist of 4 essay questions on a two-variable system of linear equations. The test results were then analyzed based on indicators of mathematical communication skills. The results of this study can provide information to teachers about students' mathematical communication skills so that teachers are expected to be able to design learning activities that can improve students' mathematical communication skills.